Effectiveness and Safety of the Sequential Use of a Second and Third Anti-TNF Agent in Patients With Inflammatory Bowel Disease: Results From the Eneida Registry. Issue 4 (29th August 2019) - Casanova, María José; Chaparro, María; Mínguez, Miguel; Ricart, Elena; Taxonera, Carlos; García-López, Santiago; Guardiola, Jordi; López-San Román, Antonio; Iglesias, Eva; Beltrán, Belén; Sicilia, Beatriz; Vera, María Isabel; et al.
Abstract: Background: The effectiveness of the switch to another anti–tumor necrosis factor (anti-TNF) agent is not known. The aim of this study was to analyze the effectiveness and safety of treatment with a second and third anti-TNF drug after intolerance to or failure of a previous anti-TNF agent in inflammatory bowel disease (IBD) patients. Methods: We included patients diagnosed with IBD from the ENEIDA registry who received another anti-TNF after intolerance to or failure of a prior anti-TNF agent. Results: A total of 1122 patients were included. In the short term, remission was achieved in 55% of the patients with the second anti-TNF. The incidence of loss of response was 19% per patient-year with the second anti-TNF. Combination therapy (hazard ratio [HR], 2.4; 95% confidence interval [CI], 1.8–3; P < 0.0001) and ulcerative colitis vs Crohn's disease (HR, 1.6; 95% CI, 1.1–2.1; P = 0.005) were associated with a higher probability of loss of response. Fifteen percent of the patients had adverse events, and 10% had to discontinue the second anti-TNF. Of the 71 patients who received a third anti-TNF, 55% achieved remission. The incidence of loss of response was 22% per patient-year with a third anti-TNF. Adverse events occurred in 7 patients (11%), but only 1 stopped the drug. Conclusions: Approximately half of the patients who received a second anti-TNF achieved remission; nevertheless, a significant proportion of them subsequently lost response. Combination therapy and type of IBD were associated with loss of response. Remission was achieved in almost 50% of patients who received a third anti-TNF; nevertheless, a significant proportion of them subsequently lost response. Abstract : Almost half of the 1122 patients who switched to a second anti-TNF after primary failure, secondary failure, or intolerance to the first anti-TNF achieved remission after switching. Factors associated with loss of response were type of IBD and combo therapy.